A Murine Model of X-Linked Moesin-Associated Immunodeficiency (X-MAID) Reveals Defects in T Cell Homeostasis and Migration - Avery, Lyndsay; Robertson, Tanner F.; Wu, Christine F.; Roy, Nathan H.; Chauvin, Samuel D.; Perkey, Eric; Vanderbeck, Ashley; Maillard, Ivan; Burkhardt, Janis K. (Frontiers in Immunology, 2022)
X-linked moesin associated immunodeficiency (X-MAID) is a primary immunodeficiency disease in which patients suffer from profound lymphopenia leading to recurrent infections. The disease is caused by a single point mutation (R171W) in the protein moesin (moesinR171W). Moesin is a member of the ERM family of proteins, which reversibly link the cortical actin cytoskeleton to the plasma membrane. Here, we describe a novel mouse model with global expression of moesinR171W that recapitulates multiple facets of patient disease. In addition to lymphopenia, these mice have systemic inflammation that is ameliorated by elimination of mature lymphocytes through breeding to RagKO. The few T cells in the periphery of X-MAID mice are highly activated and have mostly lost moesinR171W expression. In contrast, single-positive (SP) thymocytes do not appear activated and retain high expression levels of moesinR171W. Analysis of ex vivo CD4 SP thymocytes reveals defects in chemotactic responses and reduced migration on integrin ligands. While chemokine signaling appears intact, CD4 SP thymocytes from X-MAID mice are unable to polarize and rearrange cytoskeletal elements. This mouse model will be a valuable tool for teasing apart the complexity of the immunodeficiency caused by moesinR171W, and will provide new insights into how the actin cortex regulates lymphocyte function.